POTENSI PRODUKSI BIOETANOL DARI BUAH SEMU JAMBU METE (Anacardium occidantale L.) - Mustofa, Akhmad (Joglo, 2010)
Changing the status of Indonesia's oil-exporting countries to be oil importing countries was certainly a heavy burden on the state budget. Search new fuel source that could produce by the nation itself becomes a necessity. Cashewnut apple fruit production was very abundant in Indonesia. It was about 2,250,180 tons per year and most just become garbage. This fruit had a huge potential to be used as bio-ethanol. When 10% of the fruit could be used as bio-ethanol will be obtained for 225,180 tonnes of bioethanol annually.Keyword : Cashewnut apple fruit, bioethanol